5th IEEE RAS/EMBS International Conference on Biomedical Robotics and Biomechatronics 2014
DOI: 10.1109/biorob.2014.6913847
|View full text |Cite
|
Sign up to set email alerts
|

A novel muscle synergy extraction method to explain the equilibrium-point trajectory and endpoint stiffness during human upper-limb movements on a horizontal plane

Abstract: Based on the idea of synergy to explore the building blocks of movements, this study focused on the muscle space for reaching movements by human upper limbs on a horizontal plane to estimate the relationship among muscle synergies, equilibrium-point (EP) trajectories, and endpoint stiffness in two ways: (1) a novel estimation method that analyzes electromyographic signals under the concept of agonistantagonist (A-A) muscle pairs and (2) a conventional estimation method that uses mechanical perturbations. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Some of the muscle synergies contribute to the displacement of endpoint (hand) equilibrium-point (EP) and the other contributes to modulation of endpoint stiffness. We found that muscle activities during upper limb reaching movements by healthy subjects are represented by three invariant functional synergies [9]. Moreover, the muscle synergies and endpoint stiffness of the reaching movement in a post-stroke subject were different from those of a healthy subject [10].…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Some of the muscle synergies contribute to the displacement of endpoint (hand) equilibrium-point (EP) and the other contributes to modulation of endpoint stiffness. We found that muscle activities during upper limb reaching movements by healthy subjects are represented by three invariant functional synergies [9]. Moreover, the muscle synergies and endpoint stiffness of the reaching movement in a post-stroke subject were different from those of a healthy subject [10].…”
Section: Introductionmentioning
confidence: 81%
“…See [9] and [11] for more details on dynamic equations and calculation method for the parameters. (a) 2) The analysis of muscle synergy and endpoint stiffness: Human upper limbs on the horizontal plane were simplified as a two-link structure of three pairs of six muscles as shown in Fig.…”
Section: ) Estimation Of Endpoint Stiffness From Mechanical Perturbamentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the null directional muscle synergy does not contribute to the kinematics of the EP, but contributes to regulate the limb stiffness under a dynamic condition [7]. 4) Endpoint stiffness: In this model, the stiffness of each muscle is proportional to its level of activity [6].…”
Section: ) Ep Trajectoriesmentioning
confidence: 99%